Review of the genus Zeugomutilla Chen, 1957 (Hymenoptera, Mutillidae, Mutillini), with description of two new species - Lelej, Arkady S.; Williams, Kevin A.; Loktionov, Valery M.; Pang, Hong; Xu, Zai-Fu (Zootaxa, 2017)
Eight species of Zeugomutilla Chen, 1957 are reviewed. Zeugomutilla angkorensis Williams, sp. nov. (Cambodia, Thailand, Vietnam) and Z. pangi Lelej, sp. nov. (China: Hainan) are described and illustrated. A new combination is proposed for Z. spinulosa (André, 1898), comb. nov. (from Pristomutilla Ashmead, 1903). Zeugomutilla bainbriggei (Turner, 1911) and Z. horni (André, 1907) are newly recorded from India (Tamil Nadu), Z. pycnopyga Chen, 1957 is newly recorded from Thailand, and Z. saepes (Chen, 1957) from Cambodia and Thailand. An updated diagnosis of the genus and key to males and females are given.